2004
DOI: 10.1002/jcb.20239
|View full text |Cite
|
Sign up to set email alerts
|

Production of the chemokine eotaxin‐1 in osteoarthritis and its role in cartilage degradation

Abstract: The expression of the chemokine, eotaxin-1, and its receptors in normal and osteoarthritic human chondrocytes was examined, and its role in cartilage degradation was elucidated in this study. Results indicated that plasma concentrations of eotaxin-1 as well as the chemokines, RANTES, and MCP-1alpha, were higher in patients with osteoarthritis (OA) than those in normal humans. Stimulation of chondrocytes with IL-1beta or TNF-alpha significantly induced eotaxin-1 expression. The production of eotaxin-1 induced e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…The production of chemokines further stimulated expressions of their own receptors and destroyed enzymes of MMPs, which are associated with joint inflammation and cartilage degradation [Hsu et al, 2004]. Ma et al [2002] reported that GLN is an efficacious agent for suppressing activation of T-cells and dendritic cells, two crucial cells involved in immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…The production of chemokines further stimulated expressions of their own receptors and destroyed enzymes of MMPs, which are associated with joint inflammation and cartilage degradation [Hsu et al, 2004]. Ma et al [2002] reported that GLN is an efficacious agent for suppressing activation of T-cells and dendritic cells, two crucial cells involved in immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…As IL-1β and TNF-α have similar effect on the expression of many chemotaxins[14,15], we chose TNF-α as the representative pro-inflammatory cytokines in the asthmatic lung in this study. After the cells became confluent, the medium was changed to serum-free DMEM medium for 12 h. A549 cells were then exposed to increasing concentrations of melatonin (10 -10 , 10 -9 , 10 -8 , 10 -7 , 10 -6 M, the physiology concentration are 10 -9 to 10 -7 M during day and night[16]) (Sigma, St. Louis, MO, USA) and TNF-α (100 ng/ml) (Sigma), for 12 h. The cells were also stimulated with a combination of melatonin (10 -10 , 10 -9 , 10 -8 , 10 -7 , 10 -6 M) and TNF-α (100 ng/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Expression of IL-8/CXCL-8/Kc was, recently, shown to be stimulated by mechanical, inflammatory and metabolic stresses [106]. Hsu et al reported higher levels of eotaxin-1/CCL-11 in OA patients compared to controls and there was an increase in expression of eotaxin-1/CCL-11 upon treatment of chondrocytes with IL-1β and TNF-α [107]. Further, treatment of chondrocytes with eotaxin-1/CCL-11 resulted in increased expression of its receptors CCR-3 and CCR-5 and cartilage degradation enzymes MMP-3 and MMP-13 [107].…”
Section: Innate Immunitymentioning
confidence: 99%
“…Hsu et al reported higher levels of eotaxin-1/CCL-11 in OA patients compared to controls and there was an increase in expression of eotaxin-1/CCL-11 upon treatment of chondrocytes with IL-1β and TNF-α [107]. Further, treatment of chondrocytes with eotaxin-1/CCL-11 resulted in increased expression of its receptors CCR-3 and CCR-5 and cartilage degradation enzymes MMP-3 and MMP-13 [107]. Brul et al detected the expression of CCR-5 on synovial fibroblasts from OA and RA patients.…”
Section: Innate Immunitymentioning
confidence: 99%